CARB-ES-19 Multicenter Study of Carbapenemase-Producing Klebsiella pneumoniae and Escherichia coli From All Spanish Provinces Reveals Interregional Spread of High-Risk Clones Such as ST307/OXA-48 and ST512/KPC-3 - Cañada-García, Javier E.; Moure, Zaira; Sola-Campoy, Pedro J.; Delgado-Valverde, Mercedes; Cano, María E.; Gijón, Desirèe; González, Mónica; Gracia-Ahufinger, Irene; Larrosa, Nieves; Mulet, Xavier; Pitart, Cristina; Rivera, Alba; et al. (Frontiers in Microbiology, 2022)
Objectives: CARB-ES-19, a comprehensive, multicenter, nationwide study integrating whole-genome sequencing (WGS) in the surveillance of carbapenemase-producing K. pneumoniae (CP-Kpn) and E. coli (CP-Eco) to determine their incidence, geographic distribution, phylogeny, and resistance mechanisms in Spain. Methods: Seventy-one hospitals, representing all 50 Spanish provinces, collected the first 10 isolates (February to May 2019). Prevalence and incidence were calculated according to population denominators. Antibiotic susceptibility was performed using microdilution method (EUCAST). All isolates were sequenced for high-resolution single-nucleotide polymorphism (SNP) typing, core genome multilocus sequence typing (cgMLST), and resistome analysis. Results: In total, 377 (93.5%) CP-Kpn and 26 (6.5%) CP-Eco isolates were collected from 62 (87.3%) hospitals in 46 (92%) provinces. CP-Kpn was more prevalent in blood (5.8%, 50/853) than in urine (1.4%, 201/14464). The cumulative incidence for both CP Kpn and CP-Eco was 0.05 per 100 admitted patients. The main carbapenemases genes identified in CP-Kpn were blaOXA-48 (263/377), blaKPC-3 (62/377), blaVIM-1 (28/377), and blaNDM-1 (12/377). All isolates were susceptible at least to two antibiotics. Inter-regional dissemination of eight high-risk CP-Kpn clones was detected, mainly ST307/OXA-48 (16.4%), ST11/OXA-48 (16.4%), and ST512-ST258/KPC (13.8%). ST512/KPC and ST15/OXA-48 were the most frequent bacteremia-causative clones. The average number of acquired resistance genes was higher in CP-Kpn (7.9) than in CP-Eco (5.5). Conclusions: This study serves as a first step toward WGS integration in the surveillance of carbapenemase-producing Enterobacterales in Spain. We detected important epidemiological changes, including increased CP-Kpn and CP-Eco prevalence and incidence, wide inter-regional dissemination, and a shift toward high-risk clones, such as ST307/OXA-48 and ST512/KPC-3.